ILMU TAKHRIJ AL-HADITS DALAM SOROTAN:Seputar Perkembangan- Penggambaran Teori dan Praktik - Mas Rabbani Lubis, Ali Akhbar Abaib (IAIN Kediri, 2019)
This research explains the important picture that is highlighted regarding the development of the theories and practices in the science of takhrij al-hadith. The hadith is part of one of the two sources of Islamic law after the Koran. The prince of tahkhrij hadith has actually been done at the beginning of the development Ã¢â‚¬Ëœulum al-hadith, by only tracing the location of the hadith in the sources of literature or books compiled by hadith collectors. The rest regarding in-depth research on the quality of the hadith (sanad-matan) was not too carriedout by previous scholars. discourse of hadith is classified into 2 (two) types, such as: 1) discourse about the authority of the hadith as hujjah in Islamic law, and 2) study of the authenticity of the hadith itself (whether or not the Hadith itself is valid). So it is important for the next generation to be introduced to the science of takhrij al-Hadith. This has become important for Muslims to be able to connect and reveal their messages historically from the Prophet Muhammad. The author uses a literature study which introduces the methods in the takhrij al-hadith. The results of his conclusion that takhrij al-hadith had indeed been carried out by previous scholars with their respective methods, but nowadays the development and portrayal of takhrij hadith has begun to target digitalisation methods in the form of online, software or applications. For this reason, it is necessary tointroduce these technology and information-based methods while elaborating and collaborating on pre-existing methods with contemporary methods based on technology and information.Keywords: Takhrij al-Hadith, Theory, Practice